2010
DOI: 10.1007/s00414-010-0474-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of sudden cardiac death victims: a survey of current forensic autopsy practices

Abstract: Autopsy-negative sudden cardiac deaths (SCD) seen in forensic practice are most often thought to be the result of sudden arrhythmic death syndrome. Postmortem genetic analysis is recommended in such cases, but is currently performed in only a few academic centers. In order to determine actual current practice, an on-line questionnaire was sent by e-mail to members of various forensic medical associations. The questions addressed routine procedures employed in cases of sudden cardiac death (autopsy ordering, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Each country has its own law stating who should be autopsied [20]. In Denmark, we have 34 medical officers of public health and a few forensic pathologists, who together carry out all external examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Each country has its own law stating who should be autopsied [20]. In Denmark, we have 34 medical officers of public health and a few forensic pathologists, who together carry out all external examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the above recommendations for the implementation of genetic screening in the current forensic autopsy practices, a recent survey conducted mainly in European countries has shown a very limited application of genetic testing in cases of sudden cardiac death in routine forensic investigation, only 40% of the responders have the possibility to perform the genetic testing [33]. This survey also shows that many of the problems involved in the adequate investigation of SCD cases are financial in origin, Taking into account the efficiency of both MassArray strategies, it was clearly demonstrated that LQTS strategy [10], should be upgraded, since none of the mutations presented in our cases were included in the panel considered for the MassArray mutation screening; all of them were detected by direct sequencing of KCNQ1 and KCNH2 genes.…”
Section: Discussionmentioning
confidence: 97%
“…Both faiths have permitted exceptions . Alternative options include genetic assessments, or post‐mortem imaging based autopsy . While not validated for SUDEP these techniques may offer potential to exclude competing causes of death.…”
Section: Discussionmentioning
confidence: 99%